Experimental evaluation of bacterial corneal ulcer treatment plans using glucocorticosteroid - V. V. Neroev; E. V. Yani; V. A. Golikova; V. V. Pozdnyakova (Российский офтальмологический журнал)
Purpose: to experimentally evaluate treatment plans for bacterial corneal ulcers involving corticosteroid. Material and methods. We used a previously developed model of bacterial corneal ulcer. 40 rabbits (40 eyes) were divided into 4 groups of 10 rabbits (10 eyes) each. Group 1 received topical antibacterial treatment. Groups 2 and 3 additionally received 0.2–0.3 ml injections of 0.1 % Dexamethasone solution once a day (parabulbar and systemic, respectively). Group 4 (control) was clinically observed after corneal ulcer modeling, with no treatment given. The clinical picture and the dynamics of the course of the disease were assessed by biomicroscopy, a fluorescein test, photoregistration and optical coherence tomography of the anterior eye zone (Visante OCT model 1000, Carl Zeiss, Germany). To analyze inflammatory changes and corneal opacities, a quantitative scoring system has been developed. Results. Corneal opacities emerged in the 1 st group of rabbits on the 14 th day from treatment start: in groups 2 and 3, the 9 th day. In group 4, the ulcerous defect remained by day 14. In group 1, a statistically significant thinning of the cornea (by 148.2 ± 32.6 nm) was noted in the ulceration zone after 7 days. The same effect was noted in group 2 (by 363.3 ± 82.0 nm), in the 3rd group 3 (by 362.8 ± 81.2 nm), and in group 4 (by 135.9 ± 40.0 nm). In 90 % of cases in groups 2 and 3, mild corneal opacities without vascularization were formed. In other cases, corneal opacities of high or moderate degree with vascularization were observed. Conclusion. Treatment of bacterial ulcers of rabbit corneas with dexamethasone glucocorticosteroid drug reduces the recovery time as compared to the results achieved through antibacterial treatment alone, as it brings about a rapid drop in the overall inflammatory response and diameter of the ulcer, significant reduction of the edema and infiltration of the cornea, confirmed by AS-OCT. Additionally, such treatment ensures milder corneal opacity and helps avoid corneal vascularization.